The Central Library at Alasmarya Islamic University: A Field Study - bin Saad, Fatima Attia; Rajab, Emhmed M.; Al-Razizi, Fatima Salem (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
University libraries play an effective and important role in achieving the scientific goals of the university, through which traditional and modern services are provided that all libraries seek and provide effort and time for beneficiaries and researchers to find the information they need, which requires study and development, reflecting the university is interest in achieving its goals. For this reason, this study came to identify the reality of the central library at Alasmarya Islamic University in Zliten from all technical and administrative aspects in order to set out to identify weaknesses and develop a vision for the prospects for developing the library for the better and to reach results and proposals to correct it from all technical and administrative aspects.
Keywords: Library; Central Library; Information services; University; University Libraries